RI 3325 A Study Of Oxidation Of The Oil In Two Air-And Air-Gas-Repressuring Projects ? Introduction - T. W. Johnson (The National Institute for Occupational Safety and Health (NIOSH), 1937)
One of the common methods of increasing recovery of oil from partly depleted oil sands is to inject natural gas, air, or air-gas mixtures into the sand, thereby supplying energy to move oil into the well bore. Where natural gas is not available, air or an air-gas mixture is used as the repressuring medium. Air-gas mixtures are obtained from the casing-heads of oil-producing wells in the areas repressured with air or air-gas mixtures and consist usually of varying amounts of the hydrocarbon gases, nitrogen, oxygen, and carbon dioxide. Laboratory experiments have been conducted by the Bureau of Mines to determine the effect of air on crude oils.4/ In these experiments the crude oils were oxidized by the air, and the degree of oxidation depended not only upon the chemical composition of the crude oil but also upon the duration and method of contact between the oil and air, the temperature of the fluids and the concentration of the oxygen. When the crude oils were oxidized the following results and changes in the oils were obtained: